KERJA BAKTI PENATAAN ULANG SARANA PRASARANA PANTAI SEGER KUTA PASCA PANDEMI COVID-19 - Anggi Nuria Rahmawati; Baiq Ajeng Lala Wisma; Heri Setiawan; Ingga Jaya Sampurna; Emy Isnayni; Novia Nila Cahayani; Nuranjani Nuranjani; Sirwi Norma Dewi (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2023)
Kuta Lombok Village is a village located in the Pujut sub-district, Central Lombok Regency, West Nusa Tenggara, Indonesia. To reach Kuta Village, from Lombok International Airport it only takes 24 minutes for a distance of 16.4 kilometers via Jalan Raya Kuta-Lombok. This area which is located in the southern part has beautiful beaches and several attractive hills as photo locations with sparkling coastal views. The beach that is quite famous in Kuta Village is Seger beach, Seger beach is a location that is quite attractive to foreign tourists because the sea waves are very good for surfing, besides that Seger beach is also known by the outside community as the place for the bau nyale event held one once a year. However, since the Covid-19 outbreak that hit various countries in the world, including Indonesia, local and foreign tourists are not allowed to visit Seger Beach so that the facilities or infrastructure on Seger Beach become damaged and dirty. One of the efforts to improve facilities and infrastructure is rearrangement. The implementation method used is observation and direct action with the help of the community who live around Seger Beach, Ujung Lauk Hamlet, Kuta Village, Pujut District, Central Lombok. Program activities carried out include: 1) cleaning around the Seger beach; 2) painting the poles, benches and tables around the Seger beach; 3) making swings and seats; 4) making a gate for Bukit Seger; 5) and making parking lots around Bukit Seger with a thatched roof. This activity is expected to increase visitors to Seger Beach and its surroundings so that it can increase the income of the people who live there.